Pemberdayaan Kelompok Pengajian Ibu-Ibu melalui Pelatihan Produk Pangan Olahan Daging Ayam di Desa Garum, Blitar - Fajar Shodiq Permata; Dini Agusti Paramanandi; Herawati (Politeknik Piksi Ganesha Indonesia, 2026)
Animal protein intake in Indonesia remains relatively low, although chicken meat is a highly preferred protein source and can be processed into practical food products such as nuggets, katsu, chicken patties, and cilok. Women’s religious study groups (pengajian) have strong potential as a basis for family economic empowerment, yet their activities are often limited to religious rituals. The community partner in this program was the Al Husna women’s pengajian group in Garum Village, Blitar Regency, a central chicken-producing region in East Java. The program has been conducted through a community engagement project, with training in basic business economics and hands-on training in chicken-based processed foods, accompanied by technology transfer of a meat chopper, a vacuum sealer, and a 100-L freezer. This article describes community organizing, training implementation, establishment of “Baitul Husna Frozen Food”, and early reflections on the sustainability and contributions of the program to women’s skills and economic opportunities